A rapid method to assess salt marsh condition and guide management decisions. (May 2022) - Kutcher, Thomas E.; Raposa, Kenneth B.; Roman, Charles T.
Highlights: MarshRAM reflects salt marsh inundation stress and human disturbances. MarshRAM uses a novel walking-transect method to assess salt marsh integrity. MarshRAM estimates site-specific salt marsh landward migration potential. MarshRAM data can be used to prioritize salt marsh ecological interventions. MarshRAM can be adjusted to work across regions. Abstract: Salt marshes are increasingly vulnerable to degradation and loss from accelerating sea-level rise and other pervasive disturbances, spurring a need for broad, science-based information to guide management. The Salt Marsh R apid A ssessment M ethod, MarshRAM, was designed to address this need by documenting information characterizing salt marsh type, setting, ecological value, disturbance, integrity, and opportunity for landward migration at the site scale. We used the method to collect information from onsite and remote observations of thirty-one (31) salt marshes in Rhode Island, USA. MarshRAM's Wetland Disturbance Index is a checklist that ranks the intensity of individual and cumulative human disturbances, while the Index of Marsh Integrity (IMI) is generated using a novel walking-transect approach to rapidly characterize site-wide vegetation-community composition. The IMI was designed to reflect ecological response to direct disturbances and inundation stress, and our finding that IMI strongly correlates with cumulative disturbance + marsh platform elevation indicates it works as intended. A strong correlation between IMI components and historic marsh loss suggests that salt marsh community cover can also serve as an indicator of salt marsh resilience. Our study marshes diverge from accounts of historic New England salt marsh conditions in that meadow high marsh species no longer dominate the high marsh zone, Spartina alterniflora is now the dominant high marsh species, and severe edge erosion and invasion by Phragmites australis are ubiquitous. We demonstrate how MarshRAM data can be analyzed to inform restoration and conservation strategies and policy decision-making. For example, our findings suggest that inundation stress is strongly impacting marsh platform integrity, high-marsh vegetation loss is a strong indicator of degradation and vulnerability, and unassisted landward marsh migration may already be promoting resilience to inundation stress. We suggest adapting MarshRAM to meet the management needs of other regions or broader applications.